Joint Bayesian inference about impulse responses in VAR models - Atsushi Inoue; Lutz Kilian (Goethe University Frankfurt, Center for Financial Studies (CFS), 2020)
We derive the Bayes estimator of vectors of structural VAR impulse responses under a range of alternative loss functions. We also derive joint credible regions for vectors of impulse responses as the lowest posterior risk region under the same loss functions. We show that conventional impulse response estimators such as the posterior median response function or the posterior mean response function are not in general the Bayes estimator of the impulse response vector obtained by stacking the impulse responses of interest. We show that such pointwise estimators may imply response function shapes that are incompatible with any possible parameterization of the underlying model. Moreover, conventional pointwise quantile error bands are not a valid measure of the estimation uncertainty about the impulse response vector because they ignore the mutual dependence of the responses. In practice, they tend to understate substantially the estimation uncertainty about the impulse response vector.
urn:nbn:de:hebis:30:3-573886
Keywords: C22; C32; C52; 330; Loss function; joint inference; median response function; mean response function; modal model; posterior risk